The complexity of pluralistic ignorance in Republican climate change policy support in the United States - Graham Dixon; Christopher Clarke; Jeffrey Jacquet; Darrick T. N. Evensen; P. Sol Hart (Communications Earth & Environment)
Abstract Most Americans fail to recognize widespread public support for climate change action. Here we investigate how this phenomenon differs for Republican supporters versus opponents of several climate change policies. Surveying a representative sample of Republican voters (N = 1000), we find that misperception of in-group support for climate action is primarily restricted to Republicans already opposed to action. Specifically, those in the minority (i.e., Republicans opposed to climate action) were more likely to erroneously perceive other Republicans as holding views on climate change policy similar to their own. While Republican supporters recognize that most Republicans support climate change policy, they may be discouraged from expressing their support due to an information environment disproportionately portraying Republicans as opposed to climate change action.